PEMBERDAYAAN MASYARAKAT MELALUI PENYULUHAN INOVASI PEMBUATAN ABON MENGGUNAKAN IKAN LELE SEBAGAI UPAYA MENINGKATKAN UMKM dan INDUSTRI RUMAH TANGGA MASYARAKAT DESA KOTO TUO KECAMATAN XIII KOTO KAMPAR - Daffeta Fitrilinda; Rahmayuni Putri; Muhammad Nasrul Saputra; Irfan Nurdiansyah; Muhammad Zaky Naufal; Irvan Perdana Sandy; Khairun Nisak; Nikmatul Azmi; Miranda Sari; Silvia Yolanda; Muliati Muliati (Nusantara Hasana Journal, 2022)
Micro, Small and Medium enterprises (MSME or UMKM) are one of the factors that determine the increase or decrease in economic growth in Indonesia. Koto Tuo is a village with a strategic location. The village is in District XIII Koto Kampar, which has many tourist attractions. In Koto Tuo itself, there are many ingredients that can be processed into food, one of which is Catfish which can be used as a variety of processed foods, one of which is the innovation of shredded fish made from Catfish meat. The potential of this village should be very good to increase MSME or UMKM, but the lack of public knowledge about MSME or UMKM is the main problem. Counseling activity regarding the invention of shredding catfish meat may therefore be the primary remedy. Counseling activity is used to develop the local community's knowledge and soft skills. In addition, counseling includes concrete demonstrations to enhance the local community's hard abilities, particularly in the food sector to encourage MSME or UMKM. The results of the innovation counseling activity for making shredded catfish, namely the level of public knowledge increased, the Local Community interest in making a shredded catfish business also increased. And it can be concluded that the Abon (Catfish Floss) business innovation from Catfish is very appropriate for the local community of Koto Tuo.